Development of New Synthetic Strategies, Tactics and their Applications. Issue 12 (21st October 2019) - Kotha, Sambasivarao; Meshram, Milind
Abstract: This account covers our work related to the development of various synthetic methodologies since 1994. We summarized our strategies and their application to design various functional molecules. In this regard, we also report the utility of our methodologies in others research work. These methods we report here are simple and efficient for the synthesis of a wide variety of intricate molecules such as heterocycles, polycycles, unusual α‐amino acids, star‐shaped molecules, and modified peptides. For this purpose, we used various transition metal‐based reagents and catalysts. Various popular reactions such as metathesis, Suzuki coupling, [2+2+2] cyclotrimerization were used to assemble these targets. Moreover, rongalite has been used to expand the Diels‐Alder chemistry. Abstract : In this report, we have summarized various synthetic strategies that we developed in our laboratory during the past 25 years. We have shown a strategic utilization and impact of our synthetic methods in others research area.